Using Visualisations in Secondary School Physics Teaching and Learning: Evaluating the Efficacy of an Instructional Program to Facilitate Understanding of Gas and Liquid Pressure Concepts - Oh, E.; Treagust, David; Koh, T.; Phang, W.; Ng, S.; Sim, G.; Chandrasegaran, Arulsingam (Australian Science Teachers Association, 2012)
An instructional program using four simulation applets was used to facilitate understanding of gas and liquid pressure concepts among twenty-two students in a Year 9 class from an independent secondary school in Singapore. A comparison group consisting of twenty-two students was taught using traditional didactic, chalk-and-talk instruction. Administration of a gas and liquid pressure conceptual test comprising ten multiple-choice items in a pretest-posttest design indicated significant improvement in understanding using the simulation applets compared to the didactic instruction. A seven-item attitudes questionnaire indicated that the students generally found the animation applets interesting and helpful in their physics lessons.